PELATIHAN DENGAN PENDEKATAN PSIKOLOGI POSITIF: UPAYA MENINGKATKAN RESILIENSI WIRAUSAHAWAN ANGGOTA CREDIT UNION (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Entrepreneurship is an opportunity for individuals who want to have additional income apart from their regular job. Likewise, the condition of Credit Union Pangudi Luhur Kasih members who work as teachers, are expected that they can develop entrepreneurial abilities and increase their income apart from teaching. Some members who have started entrepreneurship often feel doubtful in running the business they have started, so they need to increase resilience and the business processes can be improved. Resilience webinar and group coaching with positive psychological approach will be carried out to increase the resilience of CU PLK enterpreneur members. The participants who attended the webinar were 25 people, the first coaching meeting was 8 people and the second meeting was 7 people. The lack of participants during coaching session occurred because after the webinar ended, many participants stated that they were not committed to participating in the training until the coaching session ends. However, from the results of the analysis that has been carried out, it appears that this training went well and received positive responses, although the results of the comparison of pre and post-test during the webinar showed that there was no significant change in knowledge. There was an increase in the participants' resilience scores after participating in weekly group coaching.